2018
DOI: 10.1371/journal.pone.0195197
|View full text |Cite
|
Sign up to set email alerts
|

Assessing worst case scenarios in movement demands derived from global positioning systems during international rugby union matches: Rolling averages versus fixed length epochs

Abstract: The assessment of competitive movement demands in team sports has traditionally relied upon global positioning system (GPS) analyses presented as fixed-time epochs (e.g., 5–40 min). More recently, presenting game data as a rolling average has become prevalent due to concerns over a loss of sampling resolution associated with the windowing of data over fixed periods. Accordingly, this study compared rolling average (ROLL) and fixed-time (FIXED) epochs for quantifying the peak movement demands of international r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
133
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 37 publications
16
133
1
1
Order By: Relevance
“…In particular, Vázquez-Guerrero et al (2019) showed that basketball players averaged 1.8 and 1.5 high-intensity accelerations and decelerations and covered a relative distance of 72.6 m min −1 . A similar trend has been observed in previous studies conducted in other sports, such as associated football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, Vázquez-Guerrero et al (2019) showed that basketball players averaged 1.8 and 1.5 high-intensity accelerations and decelerations and covered a relative distance of 72.6 m min −1 . A similar trend has been observed in previous studies conducted in other sports, such as associated football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…While some studies have determined the most demanding scenarios in physical demands during competition in intermittent team sports such as association football (Abbott et al, 2018;Delaney et al, 2018;Martín-García et al, 2018;Casamichana et al, 2019), rugby (Delaney et al, 2016;Cunningham et al, 2018), Gaelic football (Malone et al, 2017), and Australian football (Delaney et al, 2017) through different time average rolling durations, no studies are available that quantify physical demands during match play in basketball using this approach. A plethora of studies have examined the average (mainly per minute) and absolute physical demands of match play in basketball reporting that players usually cover 5-6 km at an average speed of 70-90 m min −1 and perform a total of 40-50 jumps (Stojanović et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the maximum average speed using a 0.1-s rolling mean for a 1min period during U18 academy RU ranged between 154 ± 17 (front row) and 185 ± 20 (scrum-half) m min −1 demonstrating substantially greater values than those presented in whole match analysis [31]. These values can be used when planning, 'live' monitoring and retrospectively analysing training so players are prepared for the 'worstcase scenario' during matches as in recently completed studies in senior international players [7,38].…”
Section: Absolute and Relative Distance Measuresmentioning
confidence: 98%
“…Whilst it might be logical for athletes to prepare in conditions which represent the mean environmental conditions in which they will be competing, for example, mean air conditions for Tokyo in August are 30-31°C,~70% RH, the authors (and others) recommend that as a minimum, athletes train in the maximum/ upper limit of environmental conditions which are forecast for the location at the time of year, for instance maximum air conditions for Tokyo in August are >34°C, >80% RH [146]. Indeed, it has been proposed that HA temperatures should be 5-10°C higher than the mean of the event location [148], in keeping with conventional training programs that mimic "worst-case scenario" game demands [149][150][151]. Athletes and practitioners should also be cautious of being reliant on mean temperatures, particularly given within day differences of~5°C are likely and events/heats may be scheduled at different times of the day [146].…”
Section: Passive Strategiesmentioning
confidence: 99%